Validation of 3D simulation tool for radio channel modeling at 60 GHz: A meeting point for empirical and simulation-based models. (15th October 2020) - Celaya-Echarri, Mikel; Azpilicueta, Leyre; Lopez-Iturri, Peio; Falcone, Francisco; Garcia Sanchez, Manuel; Vazquez Alejos, Ana
Graphical abstract: Highlights: Radio channel modelling of the millimetre wave bands has been achieved. Empirical datasets have been applied to validate simulation-based models at 60 GHz. A 3D Ray Launching simulation tool is empirically validated for 5G deployments. Radio channel characterization of complex urban environments is analyzed. Empirical-simulation interaction has been demonstrated to provide mutual benefit. Abstract: The radio channel modelling of the millimeter wave bands for the fifth generation of wireless mobile communications, appears as a challenge for both empirical and simulation approaches. In this paper we discuss the use of experimental datasets for validation of a simulation tool based on deterministic 3D ray-launching technique. The goal it twofold: validating the simulation tool and achieving more consistent results considering the restrictions and performance limits of hardware elements. A microcell canyon street scenario has been chosen for interleaving ray launching prediction and empirical analysis. Simulation results such as received power or angular distribution of path loss, as well as channel dispersion parameters such as root-mean-square delay spread have been presented. In addition, the line-of-sight to non-line-of-sight transition has been modeled as a result of the empirical-simulation interaction. Comparison of simulation and measurement results for the proposed microcellular urban scenario exhibit good agreement, validating the proposed methodology.